Glucocorticoid receptor expression is associated with inferior overall survival independent of BRCA mutation status in ovarian cancer. Issue 2 (25th January 2019) - Veneris, Jennifer Taylor; Huang, Lei; Churpek, Jane E; Conzen, Suzanne D; Fleming, Gini F
Abstract : Objective: High glucocorticoid receptor (GR) protein expression is associated with decreased progression-free survival in ovarian cancer patients and decreased sensitivity to chemotherapy in preclinical models. Prior studies suggest wild type BRCA1 promotes GR activation. The objective of this study was to characterize the relationship of tumor GR gene expression to outcome in ovarian cancer, and to evaluate the relationship of GR expression with BRCA status. Methods: Whole exome and whole genome sequencing, gene expression, and clinical data were obtained for high-grade serous ovarian cancers in The Cancer Genome Atlas. Cases with pathogenic somatic or germline BRCA1 or BRCA2 mutations were identified and classified as BRCA mutated. High or low glucocorticoid receptor expression was defined as expression above or below median of the GR / nuclear receptor subfamily 3  C1 ( NR3C1 ) gene level. Overall survival was estimated by the Kaplan-Meier method and compared by Cox regression analysis. Results: Combined germline DNA sequencing and tumor microarray expression data were available for 222 high-grade serous ovarian cancer cases. Among these, 47 had a deleterious germline and/or somatic mutation in BRCA1 or BRCA2 . In multivariate analysis, high glucocorticoid receptor gene expression was associated with decreased overall survival among ovarian cancer patients, independently of BRCA mutation status. No correlation of GR/NR3C1 gene expression with BRCA mutation status or BRCA1 or BRCA2 mRNA level was observed. Conclusions: Increased GR gene expression is associated with decreased overall survival in ovarian cancer patients, independently of BRCA mutation status. High-grade serous ovarian cancers with high GR expression and wild type BRCA have a particularly poor outcome.